Are Barbed Sutures Associated With 90‐day Reoperation Rates After Primary TKA?. Issue 11 (November 2017) - Austin, Daniel C.; Keeney, Benjamin J.; Dempsey, Brendan E.; Koenig, Karl M.
Abstract: Background: Studies have suggested that barbed sutures for wound closure in TKAs are an acceptable alternative to standard methods. However others have observed a higher risk of wound‐related complications with barbed sutures. Questions/Purposes: (1) Do 90‐day TKA reoperation rates differ between patients undergoing a barbed suture arthrotomy closure compared with a traditional interrupted closure? (2) Do the 90‐day reoperation rates of wound‐related, deep infection, and arthrotomy failure complications differ between barbed suture and traditional closures? Methods: A retrospective analysis of a longitudinally maintained institutional primary TKA database was conducted on all TKAs performed between April 2011 and September 2015. We compared 884 primary TKAs, where the arthrotomy was closed with a barbed suture, with 1598 primary TKAs closed with the standard interrupted suture. After barbed sutures were introduced at our institution in 2012, the majority of surgeons gradually switched to barbed suture closures, with many using them exclusively by the end of the data collection period. We confirmed in‐person followups and available data past 90 days for 97.4% (1556 of 1598) of the knees in patients with standard sutures and 94.8% (838 of 884) of the knees in patients with barbed sutures. Our primary endpoint was all‐cause 90‐day reoperation; our secondary endpoints considered: wound‐related reoperation, as defined by previous studies; deep infection per Musculoskeletal Infection Society guidelines; and arthrotomy failure, defined intraoperatively as an opening or dehiscence through the previous arthrotomy closure. T tests and chi‐square analyses were used to determine differences between the suture cohorts, and bivariate logistic regression was used to determine associations with our 90‐day reoperation outcomes. Results: With the numbers available, there was no association between suture type and 90‐day all‐cause reoperation (odds ratio [OR], 1.70; 95% CI, 0.82‐3.53; p = 0.156). Suture type was not associated with wound‐related reoperation (OR, 2.73; 95% CI, 0.97‐7.69; p = 0.058). A 0.6% (five of 884) arthrotomy failure rate was observed in the barbed cohort while no (0 of 1598) arthrotomy failures were noted in the traditional group (p = 0.003). Deep infections were rare in both groups (two of 884 barbed sutures, 0 of 1598 standard sutures) and could not be compared. Conclusions: Although we saw no difference in overall and wound‐related 90‐day reoperation rates by suture type with the numbers available, we observed a higher frequency in our secondary question of arthrotomy failures when barbed sutures are used for arthrotomy closure during TKA. Given the widespread use of this closure technique, our preliminary pilot results warrant further investigation in larger multicenter cohorts. Level of Evidence: Level III, therapeutic study.